Ring-1 yang Tak Berdaya: Realitas Program CSR PT. Balangan Coal di Desa Tawahan Kabupaten Balangan - Rajidin; Ismar Hamid (Prodi Sosiologi FISIP ULM, 2023)
Tawahan Village is the Ring 1 Village of PT Balangan Coal, so it is directly affected by mining activities, both social and environmental impacts. This research aims to analyse the reality of the programme implemented by PT Balangan Coal's CSR. This research uses a qualitative approach with a case study research type. The research was carried out in February-April 2023, in Tawahan Village, Juai District, Balangan Regency. Data collection techniques using observation, indepth interviews and documentation. Data analysis techniques through the stages of data reduction, data presentation and conclusion drawing. The results showed that the community empowerment program by CSR PT. Balangan Coal does not suitable with the characteristics and needs of the community. The programs implemented ignore efforts to protect the interests of the community to develop or become empowered. The positive impact of CSR Program by PT. Balangan Coal is not really felt by the community, while the negative impact of the company's activities continues to be felt by the community, such as dust, blasting vibrations, noise, and to damage community agricultural plants. Before the existence of coal mining companies, the livelihood of the Tawahan Village community depended on nature. The village government and the community hope that in the future there will be deliberations in determining the programme to suit the needs and characteristics of the community, because so far the village government and the community have not been included in determining the CSR programme to be implemented. This research provides a critical perspective on the implementation of CSR programmes that are more beneficial to the community.